268 Attitudes to STIC lesions and opportunistic salpingectomy: is there a role in the general population?. (18th September 2019) - Agnew, H; Brown, A; Harley, I
Abstract : Objectives: The fallopian tube is well recognised as the site of origin of high-grade serous carcinoma (HGSC) and their precursor serous tubal intraepithelial carcinoma (STIC). Bilateral salpingo-oopherectomy is recommended as risk reduction surgery in the high risk population, however the protection offered by opportunistic salpingectomy in the general population remains undetermined. We assessed attitudes among consultant obstetrician/gynaecologists to STIC and performing opportunistic salpingectomy in those without a defined genetic risk. Methods: An anonymous online survey was sent to consultant obstetrician/gynaecologists in Northern Ireland. The questions aimed to determine their understanding of STIC, barriers to counselling patients and performing opportunistic salpingectomy in 3 specific scenarios: caesarean section sterilisation, vaginal hysterectomy and sterilisation requests. Results: 62.3% consider their knowledge either average or poor. 55.1% feel 'somewhat confident' in counselling patients, with main barriers being lack of knowledge, lack of clear evidence and thus no accurate risk/benefit ratio. 68%, 67% and 77% would consider carrying out opportunistic salpingectomy at caesarean section sterilisation, vaginal hysterectomy and for sterilisation respectively. Those against state fertility concerns, lack of evidence and increased complications. Conclusions: There are still significant gaps in knowledge regarding STIC among consultants in Northern Ireland, which effects their willingness to consider opportunistic salpingectomy at the time of other operations. If these gaps and their concerns are addressed, there may be an impact on the potential benefit of performing this procedure in reducing the incidence of HGSC. Acknowledgements: The Ulster Obstetrical&Gynaecological Society, Dr. P.Birkett, Dr. J.Breen, Dr. K.Devlin, Dr. R.Farr, Dr. A.McNally and Dr. A.Wilson, for encouraging responses.